Data-driven Content Marketing Implementation: Increasing Engagement through SEO on Social Media - Falah, Zidnal (Politeknik Siber Cerdika Internasional, 2025)
The rapid development of the digital world has changed the pattern of interaction between companies and audiences, demanding more adaptive and data-driven marketing strategies. One increasingly important approach is the integration of data-driven content marketing and search engine optimization (SEO) to increase engagement on social media. This research aims to analyze how the implementation of data-driven content marketing combined with SEO can increase audience engagement, as well as identify supporting and inhibiting factors in its implementation. The research method used is descriptive qualitative, with data collection techniques in the form of in-depth interviews, observation, and documentation of digital marketing practitioners in the creative industry and e-commerce sectors. The results showed that the data-based content marketing strategy integrated with SEO was able to significantly increase engagement, as shown by the increase in likes, comments, shares, and saves on social media. The main supporting factors are the use of data analytics and managerial support, while inhibiting factors include changes in social media algorithms and limited human resources. In conclusion, the integration of data-driven content marketing and SEO is an effective strategy in increasing digital audience engagement. The implications of this research emphasize the importance of technological adaptation and strengthening team capacity in the face of evolving digital platform dynamics.